Rereading the Ungers: Utopian Realism as a Basis for Contemporary Urban Design - Ciambellotti, Chiara (Histories of Postwar Architecture, 2023)
Although much has been said about the work of Oswald Mathias Ungers, this essay aims to address the decade from ‘67 to ‘77, which saw the departure of the Ungers family for the United States of America, more precisely for the city of Ithaca in the state of New York. It was precisely the American period that allowed O.M. Ungers to reflect and revise much of the work that had seen him directly involved in some controversies, which culminated in protests in December ‘67. The purpose of this text is to briefly review some of the events that took place during that period, in order to shed light on two almost unknown texts that saw their birth mainly thanks to the American period and the social ferment of the time: Kommunen in der Neuen Welt. 1740 - 1972, published in ‘72 by both authors and Die Rückkehr des Roten Mannes: Indianer in den USA, published in ‘74 by Liselotte Ungers. It is essetial to point out these publications, not only to bring to light a part of Ungers’ work unknown to most, but also to clarify some of the urban strategies proposed by O.M. Ungers that become, now more than ever, fundamental references for the possible resolution of contemporary crises. In a period that sees the rediscovery of utopia as a model for solving the many crises we are facing, as was already the case in the 1960s and 1970s, it is appropriate to recall and deepen Ungers’ reflections on the Utopian device trying not to fall back on the proposal of sci-fi or retro-futuristic models.